Landscape architectural graphic standards - Hopper, Leonard J. (Hoboken, N.J. : John Wiley & Sons, 2007)
Landscape Architectural Graphic Standards, Student Edition is an abridged version of Landscape Architectural Graphic Standards._This book focuses on the practical skill set required of graduates of landscape architecture programs entering the workforce. Topics covered include site analysis and design, construction techniques, plant identification, grading and drainage. This helpful reference provides all the critical and practical material students need for the core classes required by all curriculums.
Includes index.
boek